Analysis of ambient airborne mycoflora around Curzon hall campus, University of Dhaka, Bangladesh (Stamford Journal of Microbiology, 2020)
The indoor and outdoor air is an important source of aeroallergens and pathogens. Monthly samplings were recorded during September to November 2018 to investigate the airborne mycoflora concentration in Curzon hall campus, University of Dhaka. The fungal colonies developed in Potato Dextrose Agar (PDA) media were isolated from four different locations in the morning, noon and evening in monthly intervals. A total number of counted fungal colonies were 2,681 in which 924, 928 and 829 colonies were found in the morning, noon and evening time, respectively. Among the identified fungi, Aspergillus spp. was one of the most predominant genera in all the stations over the study period followed by Penicillium spp. Alternaria spp., Curvularia spp., Fusarium spp., Rhizopus spp. and Trichoderma. The identified fungi belonged to eight genera under the class Ascomycetes, Zygomycetes and Deuteromycetes. Among the fungal isolates, Alternaria spp., Aspergillus spp., Curvularia spp., Fusarium spp., Penicillium spp. and Rhizopus spp. were previously reported as pathogenic to plants and/or humans and strongly allergenic to human being.Stamford Journal of Microbiology, Vol.9(1) 2019: 32-35